PERTANGGUNGJAWABAN PIDANA RC YANG MEMBERIKAN KETERANGAN SECARA MENYESATKAN KEPADA PENERIMA FIDUSIA DITINJAU DARI UNDANG-UNDANG NOMOR 42 TAHUN 1999 TENTANG JAMINAN FIDUSIA - MAHARANI AMALIA PUTRI; Sriwati Sriwati; Ida Sampit Karo K. (CALYPTRA, 2018)
The purpose of writing this scientific journal is as a requirement for graduation and obtaining a law degree at the Faculty of Law of the University of Surabaya. Practical Objectives of the writing of this thesis to be able to know Whether RC that gives misleading information to fiduciary recipients may be sought criminal responsibility in terms of Article 35 of Law Number 42 of 1999 on Fiduciary Guarantee. RC acts have fulfilled the elements contained in Article 35 of the Fiduciary Guarantee Act, namely RC deliberately misrepresents the ownership of the motorcycles purchased to PT. Adira Finance as the recipient of fiduciary so that gave birth Fiduciary Guarantee agreement with Number: W1300192796.AH.05.01 Year 2014 dated March 7, 2014 on behalf of RC. The acts committed by the RC have fulfilled the elements of error contained in criminal responsibility, namely the existence of unlawful acts, the ability to be accountable to the perpetrator, has a form of mistake in the form of intent as a necessity or a certainty and no excuse of forgiveness to the perpetrator. RC acts is a continuing act as stipulated in Article 64 paragraph (1) of the Criminal Code, violating Article 372 of the Criminal Code and Article 35 of the Fiduciary Guarantee Act, RC shall be liable to a maximum imprisonment of 1 (one) year and a maximum of 5 (five) years and a fine At least Rp. 10.000.000, - (ten million rupiah) and at most Rp.100.000.000, - (one hundred million rupiah) as stipulated in Article 35 of the Fiduciary Guaranty Ac.